1997
DOI: 10.1111/j.1525-1594.1997.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Platelet Activation by Different Cellulosic Membranes

Abstract: rapid increase at 45 min HD reverting to baseline at 120 min HD. The degree of echinocytosis may inversely affect the ESR. Because echinocytes have a negative influence on the ESR and the number of echinocytes fluctuates during dialysis, for the ESR to have diagnostic value, it is necessary to determine the number of echinocytes and the ESR simultaneously. ReferencesBrecher G, Be& M. Present status of spiculated red cells and their relationship to the disco-echinocytes transformation: A critical review. Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Complement activation and platelet–neutrophil coaggregate formation are interrelated, since C5a and C3a, generated by complement activation, induced neutrophils to express adhesion molecules and to promote platelet–neutrophil adhesion. Several reports have in fact shown that RC membranes induce the activation of platelets during hemodialysis 32–34. The platelet activation by these membranes is possibly mediated by intricate processes involving complements and leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation and platelet–neutrophil coaggregate formation are interrelated, since C5a and C3a, generated by complement activation, induced neutrophils to express adhesion molecules and to promote platelet–neutrophil adhesion. Several reports have in fact shown that RC membranes induce the activation of platelets during hemodialysis 32–34. The platelet activation by these membranes is possibly mediated by intricate processes involving complements and leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Активация каскада свертывания крови и тромбообразования может быть обусловлена контактом крови с экстракорпоральной системой в ходе ГД. Этот эффект особенно характерен для диализаторов на основе купрофана и менее и выражен при использовании других мембран [123,124]. Тромбообразование менее выражено при использовании фракционного гепарина, чем нефракционного [34].…”
Section: нарушения коагуляцииunclassified
“…, cytokine production [3,4] , protein absorption [5] , platelet activation [1,6,7] , and oxidative stress [8][9][10] .…”
Section: Upar (Cd87) As a Biocompatibility Marker Of Dialysis Membranementioning
confidence: 99%